Implementasi Strategi Transformasi Digital Berbasis Analisis SWOT melalui Modul Inovasi Pengelolaan Manajerial pada UMKM Tahu Goreng ABA - Satrio Ahmadtul Firdaus Romadhoni; Dikie Egie Nugraha; Agus Hermawan; Agung Winarno (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
The development of digital technology has changed the operational paradigm of Micro, Small, and Medium Enterprises (MSMEs), including the culinary sector. However, most MSMEs still face limitations in adopting digital-based management systems. This study aims to implement a SWOT analysis-based digital transformation strategy through the development of a Managerial Innovation Module for the "ABA" Fried Tofu MSME in Malang City. The method used is a descriptive qualitative approach with a Participatory Action Research (PAR) model for three months. Mentoring is carried out through five main aspects: SWOT analysis, product innovation, digital marketing, human resource and financial management, and production waste management. The results show a significant increase in production efficiency, brand image strengthening, market expansion, and increased awareness of environmental sustainability. The implementation of the digital-based innovation module has proven effective in encouraging adaptive, sustainable, and competitive managerial transformation in the digital economy era.